An inquiry on north-eastern Italian farmers’ perception of climate change and related risks to agriculture - Nassivera, Federico; Gallenti, Gianluigi; Carzedda, Matteo (Italian Review of Agricultural Economics, 2022)
Even though agricultural activities have always had to face systemic risk, increasing uncertainty linked to market conditions, policy revision and climate change require the adoption of extensive, functional and informed risk management strategies. Our study aims to investigate north-eastern Italian farmers’ perception of climate change-related risks and attitudes towards adaptation strategies, in order to promote the adoption of effective communication strategies and the development of more attractive insurance schemes to widen famers’ interests. Cross-sectional survey data were analysed using structural equation modelling to explore concerns over the impact of climate change on agricultural activities and identify the factors that promote the adoption of coping strategies. According to the results, the actual experience of negative consequences linked to specific extreme meteorological events is the main driver for the adoption of mitigation strategies. Further efforts on awareness of climate change and its consequences, coupled with the provision of simpler and more tailored insurance schemes, are required to support a widespread diffusion of adaptation strategies among farmers.